Proposed upgrading of Bahtera Nelayan Restaurant for Persatuan Nelayan Kuala Kedah , at Kampung Kelunchor, Mukim Kubang Rotan, 06250 Alor Star, Kedah Darul Aman / 'Aifaa Hanisah Abd Razak - Abd Razak, 'Aifaa Hanisah (Faculty of Architecture, Planning and Surveying, 2010)
The final project for the student of Diploma in Interior Architecture is give the student knowledge about every aspect on interior design. This is the final project proposal to upgrade the interior design for the Bahtera Nelayan Restaurant. Purpose this study was to find out more about the restaurants in Malaysia and overseas. Concepts and images are selected not only according to the customer, it will reflect the identity of the customers and the client itself. It will also enhance business performance with a positive impact. Besides this restaurants the purpose also to introduce an atmosphere of fishermen and the boat is in addition to inhaling the fresh air and comfortable. The restaurant is also to give customers a taste of dishes in the space. To launch this project, there is some information obtained from this study site selection studies, internet, interview studies, observation studies, case studies and research to make study. Purpose question is to examine the strengths and weaknesses in the design of the interior of the restaurant. These studies and data collection will be applied in the design process to obtain a comfortable and attractive design.